The effectiveness of final intraoperative endoscopic control in conventional septoplasty - Bayraktar, Cem; Dogan, Sedat (The European Research Journal, 2016)
Objective. Septoplasty operation is a very common procedure and can be performed with endoscopic or conventional techniques. In some cases, preoperative nasal endoscopy can not be performed due to severe anterior deviations, and computerized tomography assessment causes to radiation exposure and increased cost. Our aim was to investigate the effectiveness of final endoscopic control in conventional septoplasty operations.Methods. Fifty-one subjects who underwent conventional septoplasty with intraoperative endoscopic control and thirty age-sex matched patients who were being performed conventional septoplasty without endoscopic control were enrolled in this prospective study. Surgeon satisfaction intraoperatively and patient satisfaction 3 months later from surgery obtained with using 5 point Likert scale. Additional pathologies which observed by using intraoperative endoscopy and the rate of performed additonal surgeries were recorded.Results. Using this technique, surgeon satisfaction improved (p=0.02), but there was no significant difference on patient satisfaction (p=0.642). Additional pathologies were seen in 25% of patients and additonal surgeries performed in 21% of patients. All observed additonal pathologies were diagnosed and treated with endoscope easily.Conclusion. Final intraoperative endoscopic control in conventional septoplasty is an effective method and improves the surgeon satisfaction in surgery.